Peculiarities of Product Placement in Movies: Theoretical Aspect (Laisvalaikio tyrimai, 2018)
Research background. According to J. A. Karrh et al. (2001) product placement in movies is used with intensions to extend product awareness, create positive associations with a product, or to promote sales. Product placement is becoming very successive tool of promotion; its impact on society is constantly growing. Many films can make an impact on society’s attitudes, also, form buying patterns. Despite a wide usage of this promotional tool, attempts to find scientific publications of Lithuanian authors considering this product placement in Lithuanian movies were unsuccessful. However, many cases of product placement can be observed in Lithuanian movies. Therefore, it becomes relevant to analyze the peculiarities of product placement in movies. The problem solved in the article is how to make product placement in movies. Foreign authors are constantly providing research on multiple aspects of product placement (its impact on viewers’ purchase intentions, impact on memorization, product awareness, etc.); therefore, the lack of Lithuanian researches in the field substantiates the problem. The object of the article is the peculiarities of product placement in movies. The aim of the article is to reveal the peculiarities of product placement in movies. Research method. Qualitative content analysis of scientific literature was provided to reveal the principal aspects of product placement in movies. Whereas there is a lack of Lithuanian authors’ insights in the field, researches provided by foreign authors (Sargent et al., 2001; Jin, Villegas, 2007; Sung et al., 2008; Wiles, Danielova, 2009 et al.) were analyzed. Various approaches to product placement in movies provided by different authors are reviewed, different conceptions of product placement in the movies are generalized, and potential usage areas of the activity are revealed in the article. General scientific research methods of logical analysis and synthesis of scientific literature are applied for theoretical research. Findings. Product placement in movies can be named as an alternative way to reach target audience and highlight product’s advantages. Product placement is product’s or its identifier’s inclusion into media using sonic or visual elements. The main goal of product placement is to increase customer awareness, make positive impact on their preferences and purchase intentions. Main advantages of product placement in the movies are naturalness, high concentration of viewer’s attention, inevitability, and revelation of character, creation of positive associations, sales promotion, and the reach of target audience. Scientific researches and real practices of foreign organizations have proven that product placement in the movies enhance product awareness, creates and increases positive impact on a brand. Accordingly, the direct impact on increase in sales can be observed.Keywords: advertising, promotional tools, sales promotion.